Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.6 - Radical Equations and Problem Solving - Exercise Set: 50

Answer

no solution

Work Step by Step

Squaring both sides of the given equation, $ \sqrt{x+1}-\sqrt{x-1}=2 ,$ results to \begin{array}{l}\require{cancel} (\sqrt{x+1}-\sqrt{x-1})^2=(2)^2 \\ (\sqrt{x+1})^2-2(\sqrt{x+1})(\sqrt{x-1})+(\sqrt{x-1})^2=4 \\ x+1-2\sqrt{x+1}\sqrt{x-1}+x-1=4 \\ (x+x)+(1-1-4)=2\sqrt{x+1}\sqrt{x-1} \\ 2x+4=2\sqrt{x+1}\sqrt{x-1} \\ \dfrac{2x+4}{2}=\dfrac{2\sqrt{x+1}\sqrt{x-1}}{2} \\ x+2=\sqrt{x+1}\sqrt{x-1} .\end{array} Squaring both sides for the second time results to \begin{array}{l}\require{cancel} (x+2)^2=(\sqrt{x+1}\sqrt{x-1})^2 \\ (x)^2+2(x)(2)+(2)^2=(x+1)(x-1) \\ x^2+4x+4=x^2-1 \\ (x^2-x^2)+4x=-1-4 \\ 4x=-5 \\ x=-\dfrac{5}{4} .\end{array} If $x=-\dfrac{5}{4},$ then the part of the original equation, $-\sqrt{x-1},$ results to a negative radicand. This is not defined for the set of real numbers. Hence, there is no solution.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.